Mathematics
Without using trigonometric tables, prove that:
sin 63° cos 27° + cos 63° sin 27° = 1
Answer
To prove,
sin 63° cos 27° + cos 63° sin 27° = 1
Solving, L.H.S. of the equation we get,
⇒ sin (90° - 27°) cos 27° + cos (90° - 27°) sin 27°
We know that,
sin (90 - θ) = cos θ and cos (90 - θ) = sin θ
⇒ cos 27° cos 27° + sin 27° sin 27°
⇒ cos2 27° + sin2 27°
⇒ 1.
Since, L.H.S. = R.H.S.
Hence, proved that sin 63° cos 27° + cos 63° sin 27° = 1.
Related Questions
Without using trigonometric tables, prove that:
cosec2 67° - tan2 23° = 1
Without using trigonometric tables, prove that:
sec2 22° - cot2 68° = 1
Without using trigonometric tables, prove that:
sec 31° sin 59° + cos 31° cosec 59° = 2.
Without using trigonometric tables, prove that:
sec 70° sin 20° - cos 20° cosec 70° = 0